Compressive and tensile strength of aeolian sand stabilized with porcelain polishing waste and hydrated lime - Silva, José; Santos Júnior, Olavo; Paiva, William (Soils & rocks, 2023)
The improvement of sandy soils by incorporating new stabilizing agents in a physical and/or chemical process has become the subject of many studies in recent decades. In addition, the use of industrial wastes in this process can bring significant benefits to the environment and savings in natural resources. This work aims to evaluate the implications of incorporating porcelain polishing waste (PPW) and hydrated lime on the mechanical properties of an aeolian dune sand from the city of Natal/RN. Tests of unconfined compressive strength and split tensile strength were performed on compacted soil specimens with different contents of PPW (10%, 20% and 30%), hydrated lime (3%, 5% and 7%) and relative densities (25%, 50% and 75%). To evaluate the effects of each factor, the Response Surface Methodology with Central Composite Design was used. The results have shown that all three factors have a positive effect on the response variables. The highest strengths were obtained in regions combining high values of relative density and PPW content and an optimum lime content was found. An inversely proportional correlation and good fit to the experimental data was obtained between the strength values and the porosity/binder index (η / Biv). The strength gains were attributed to densification of the soil structure and cementation of the particles by the compounds formed in the reaction between lime and PPW. The results also showed an increase in the strength with curing time, indicating a pozzolanic activity of the mixtures.